Tinjauan Yuridis Terhadap Pembatalan Merek dengan Persamaan pada Pokoknya: Kasus Gudang Garam VS Gudang Baru di Indonesia(Studi Putusan Nomor 4/Pdt.Sus-HKI/Merek/2021/PN Niaga Sby) - Pilihan Fredrick Johannes Tanjung; Venia Utami Keliat (CV WAHANA PUBLIKASI, 2026)
This study aims to examine the application of the principle of similarity in essential elements as a basis for trademark cancellation in a dispute involving prominent cigarette trademarks in Indonesia, in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The research employed a normative juridical method using a case study approach centered on the decision of the Surabaya Commercial Court Number 4/Pdt.Sus-HKI/Merek/2021/PN Niaga Sby. The findings indicate that the judges adopted a substantive approach in assessing trademark similarity based on the overall impression created in the minds of consumers. Although the decision strengthens protection for trademark owners, the analysis reveals weaknesses in the juridical reasoning, as the parameters for visual, phonetic, and conceptual assessment were not explicitly formulated. This study concludes that there is a need for the standardization of assessment parameters by judges in order to create legal certainty for business actors in Indonesia.